Caesarean delivery on maternal request: need to redefine in view of intrapartum cases - Atnurkar, Kishore Bhanudasrao; Mahale, Arun Ramkrishnarao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The objective of the study was to analyse the data of caesarean section on maternal request (CDMR) both before labour and intrapartum, in low-income society from a town in India. Methods: It was a retrospective observational study of 9331 caesarean section (CS) cases carried out in different small private maternity hospitals over a period of 20 years. We used the data for auditing the CS cases done on maternal request. Results: Out of 9331 CS cases documented, 216 CS were done on maternal request. The incidence of CDMR was 2.31%. About one third cases were intra-partum. The rising trend of CDMR was observed both before labour and intra-partum. Conclusions: There was a need to redefine CDMR in the view of rise in the incidence of women requesting for CS not only before labour but during lab or also. CDMR is no more confined to highly educated, rich and women from urban area. Less educated, low income group women residing in rural area are also becoming aware that CS can be done on maternal request.